Perhitungan Neraca Massa pada Sistem Kolom Distilasi dengan Umpan Fatty Acid - Ratna Kristina Tarigan; Fernando Nainggolan; Helisa Amanda Sidabutar (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
Distillation is a separation method used to isolate fatty acid components based on differences in their boiling points. This process is carried out using three distillation columns operating under different pressure and temperature conditions. The first column operates at a pressure of 12–14 mbarA and a temperature of 245–246 °C, the second column at 5–6 mbarA and 247–248 °C, and the third column at 14–15 mbarA and 268–270 °C. The main products from the first and second columns are obtained from the middle fraction, namely the fatty acids FA1698 and FA1865. Meanwhile, the third column is used to separate the heavy-end components (C16, C18, C20, and unidentified compounds) from the residue, forming Mixed Acid Oil (MAO). This study focuses on mass balance analysis to determine the mass flow rates and composition of the bottom fraction in each distillation column. The results show that the first column produces a bottom product of 7092.5 kg/h, with stearic acid (65.53%) and palmitic acid (33.19%) as the dominant components. The second column yields 393.25 kg/h, with the major components being stearic acid (55.02%) and palmitic acid (32.37%). The third column produces an MAO residue of 162.25 kg/h, primarily consisting of stearic acid (48.61%) and palmitic acid (28.88%).